Aplicación de un proceso tecnológico para la obtención de una bebida emoliente a partir de la Linaza, Sábila y Cola de Caballo para consumo humano. - Porras Romero, Yingo V. (2015)
This research stems from the initiative of seeing vendors emollient waters known as aromatic waters which manufacture them in the open and are contaminated, thus obtained the following investigation with the aim of implementing a technological process to this drinks to obtain a final product of good quality which in the future could compete in the energy market or commercial beverages, emerging several options as sources of raw material, the mixture being chosen Linseed (Linum scientist), Aloe(Aloe barbadensis)and Cola(Equisetum giganteum L)